Computational study on the effect of orifice-edge-chamfered angle on the synthetic jet characteristics. (26th November 2019) - Hoh, Hong Mun; Yuan, Cheng See; Soon, Teo Yong; Chuan, Lim Kim
The effect of chamfered orifice edges on the time-averaged pressure difference and jet velocity of synthetic jet have been numerically investigated. Chamfered orifice edges with exit angle of 15° and 30° are analysed. Moving grid is utilised to define the moving diaphragm of the actuator. The results are validated against experimental data. The time-averaged pressure difference between the location inside the orifice duct and downstream region where the velocity becomes negligible have been numerically predicted for all the cases. The jet velocity is predicted numerically at the downstream location of 1 mm from the orifice exit. The overall results indicated that the changes of chamfered orifice edges give significant impact on the time-averaged pressure difference. The jet velocity is also affected by the variation of the chamfer orifice edges during the expulsion stage. The findings from this study provides a basic design guideline for designing a synthetic jet actuator with lower minor loss and power dissipation.